Adaptation of voltage degree of regulatory systems to active physical activity in children with cerebral palsy - Gross N.A.; Khrekin D.O.; Sharova T.L.; Klendar V.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to study the level of adaptive capabilities of the body of children with cerebral palsy based on the analysis of heart rate variability (HRV), determined before and after performing active physical exercises in a rehabilitation session. Methods and structure of the study. The scientific work involved 303 children aged 5 to 14 years with a diagnosis of cerebral palsy and different levels of development of gross motor functions according to the international GMFCS scale. The frequency of occurrence (in %) of indicators of activity of regulatory systems (IARS) and indicators of functional resources in children before and after performing active physical activity was analyzed. Results and conclusions. A low level of initial functional reserve and insufficient activity of the cardiovascular system were revealed, which should be taken into account when conducting classes. Adaptive reactions in children with varying degrees of disease severity are individual and are implemented in different ways. It was revealed that individually selected physical activity increases the activation of regulatory systems and functional resources in children with cerebral palsy, especially with severe motor impairments (level 4-5 of the GMFCS scale). To develop functional and physical abilities in children with cerebral palsy, continuous physical rehabilitation is necessary, as a result of which the body’s capabilities gradually increase and long-term adaptation is formed, associated with the activation and mobilization of functional resources.